NUMERICAL ANALYSIS OF SAFETY ZONE OF A LARGE FLAT-PLATE BOUNDED-WAVE EMP SIMULATOR. Issue 2 (11th December 2019) - Huang, Liuhong; Meng, Cui; Li, Yuebo; Yang, Jie; Xiong, Jiuliang; Wu, Ping; Jiang, Yunsheng
Abstract: The safety zone of a large flat-plate bounded-wave electromagnetic pulse simulator was analyzed using the 3D electromagnetic simulation software Computer Simulation Technology. First, the double-limit requirement cited from the GB 8702 for an instantaneous pulse was clarified compared with the International Commission on Non-Ionizing Radiation Protection guidelines. This means that both the amplitude of the time-domain waveforms and all frequency components should be satisfied with the respective exposure limits. Then, the leakage field of a large flat-plate bounded-wave simulator was simulated. After analyzing the peak amplitude of an instantaneous electric field in a certain area, the observation points along six directions were specified, and the corresponding amplitudes were given. Furthermore, it was verified that the time-domain electric field of the critical points was satisfied with the frequency-domain exposure limits. Finally, the safety distances lower than the reference levels were given, and the safety zones corresponding to the three common exposure limits were obtained.